A Problem-Based Learning Mobile Application to Enchance Mathematics Problem-Solving Skills - Wiryanta, Nyoman Agus; Agustini, Ketut; Parwati, Ni Nyoman (Universitas Pendidikan Ganesha, 2024)
Students' varying abilities in solving mathematical problems significantly impact their understanding of mathematical concepts. Limited comprehension among students often leads to learning difficulties and an inability to effectively engage in the learning process. This study aims to develop a problem-based learning (PBL) mobile application designed to improve the mathematical problem-solving skills of eighth-grade students. This research adopts a development approach using the 4D (Define, Design, Develop, and Disseminate) model. The research subjects include content experts and instructional design experts. Trial subjects consist of 10 students for a small group trial and two entire classes for the large group trial. Data collection methods involve questionnaires and tests. The instruments used include the LORI (Learning Object Review Instrument), the UEQ (User Experience Questionnaire), and problem-solving tests. Data analysis was conducted using qualitative analysis, quantitative analysis, and t-tests. The results indicate that the developed mathematics mobile application has been validated as effective by experts and deemed practical by end users, including teachers and students. The t-test results reveal a significant difference in students’ problem-solving abilities before and after the implementation of the mobile application as a learning medium based on the problem-based learning model. It can be concluded that the use of the mathematics mobile application leads to an improvement in students’ academic performance in mathematics. The implication of this research is that the developed problem-based learning mobile application can facilitate students’ learning processes and enhance their understanding in solving mathematical problems.